The Impact of Field Work Practices and Learning Motivation on Student Learning Outcomes - Nurwasilatusaniah, Nurwasilatusaniah; Fitria, Happy; Wahidy, Achmad (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to determine 1) the effect of fieldwork practices on student learning outcomes, 2) the effect of learning motivation on student learning outcomes, 3) the effect of fieldwork practices and learning motivation simultaneously on student learning outcomes. The method used by researchers in this research is descriptive analysis method, while the population studied was Class XII students at Tri Bhakti At-taq'wa Health Vocational School Ogan Komering Ilir district, totaling 101 students. The data collection techniques were questionnaires and interviews. The analysis technique used in this study is the t-test and the F test with SPSS version 20.0 as supporting instrument. The results of this study indicate that 1) there is a significant impact between fieldwork practices on student learning outcomes 2) there is a significant impact between learning motivation on student learning outcomes 3) there is a significant impact between fieldwork practices and learning motivation simultaneously on student learning outcomes